2017
DOI: 10.1186/s12879-017-2895-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of healthcare worker hands and portable medical equipment: a sequence analysis to show potential transmission opportunities

Abstract: BackgroundWhile research has demonstrated the importance of a clean health care environment, there is a lack of research on the role portable medical equipment (PME) play in the transmission cycle of healthcare-acquired infections (HAIs). This study investigated the patterns and sequence of contact events among health care workers, patients, surfaces, and medical equipment in a hospital environment.MethodsResearch staff observed patient care events over six different 24 h periods on six different hospital unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 17 publications
3
56
1
2
Order By: Relevance
“…We found that the patient was the most commonly touched surface, contacted in 91% of the visits, which is consistent with the work of others [8,9,12,13]. Bed surfaces, bed rail, IV pole, computer station, and tray table were among the most highly touched fomites by both HCWs and patients in this study, which is consistent with the work of others [8,9]. The median contact rate on all fomites by HCWs was 37.8 contacts per hour, which is lower than the 93.1 contacts per hour reported by Cheng et al [9].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that the patient was the most commonly touched surface, contacted in 91% of the visits, which is consistent with the work of others [8,9,12,13]. Bed surfaces, bed rail, IV pole, computer station, and tray table were among the most highly touched fomites by both HCWs and patients in this study, which is consistent with the work of others [8,9]. The median contact rate on all fomites by HCWs was 37.8 contacts per hour, which is lower than the 93.1 contacts per hour reported by Cheng et al [9].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, these data indicate that HCWs contact surfaces similarly when providing routine care to patients with viral respiratory infections and other infectious diseases. We found that the patient was the most commonly touched surface, contacted in 91% of the visits, which is consistent with the work of others [8,9,12,13]. Bed surfaces, bed rail, IV pole, computer station, and tray table were among the most highly touched fomites by both HCWs and patients in this study, which is consistent with the work of others [8,9].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The effect of manual cleaning is variable and cleaning is often incomplete even after an intervention to improve cleaning methods [5]. Medical devices used by multiple patients are often inadequately cleaned by manual measures [6]. Therefore automated cleaning systems, such as pulsed xenon ultraviolet (PX-UV), are innovations designed to disinfect hospital environments of different settings, such as wards [7][8][9][10][11], burns units [12], milk feed preparation rooms [13], operation rooms [14,15], surgical sites [16,17], nursing homes [18], long-term acute care facilities [19], isolation rooms [20], and community hospitals [21,22].…”
Section: Introductionmentioning
confidence: 99%